Howard Zinn you can't be neutral on a moving train - Ellis, Deb.; Mueller, Denis; Damon, Matt.; First Run Features (Firm) (New York, N.Y. : First-Run Features, 2004)
Historian, activist, and author Howard Zinn loves his country. This does not mean he refrains from reproaching it for its crimes; such reproach is one of the spurs to it doing better one day soon. To that end, Zinn became an academic. However, as the child of poor, working-class parents, Zinn has also been a blue-collar dockworker and labor organizer, a decorated WW2 bombardier, an adviser to the Student Non-Violent Coordinating Committee and leader of the peace movement at Boston University in the 1960s. Zinn is the rare historian who's been brave enough to participate in the making of history, and this film finds him returning to the role of anti-war activist in post 9/11 America, asserting the value of nonviolent civil disobedience, and the need for ''people's movements'' to effect social change.
Introduction -- Early life -- Power of labor -- Roz -- Royan -- Early married life -- Ludlow Massacre -- South -- Dunkin Donuts -- New Abolitionists -- Vietnam -- Logic of Withdrawal -- Role of the historian -- Civil disobedience -- Zinn and Silber -- People's History -- Marx in Soho -- War is like crack -- Democracy -- Credits.
DVD.
Howard Zinn; interviewees include Oscar Chase, Alice Walker, Marian Wright Edelman, Noam Chomsky, Staughton Lynd, Cleveland Sellers, Bob Moses, Clayborne Carson, Tom Hayden, Stanley Kutler, Daniel Ellsberg, Dan Berrigan, Jay Craven, Ray Mungo, Francis Fox Piven, Elsa Misson; narration, Matt Damon.
Music composed by Richard Martinez.
Originally released as a motion picture in 2004.
Special features: Biographies: Filmmakers Deb Ellis and Denis Mueller [text feature]; Human nature and aggression (9 min.); Speech at Veterans for Peace Conference 2004 (16 min.); 1971 Speech at Boston Common of (sic?) civil disobedience (12 min.) [Audio-only feature]; trailer gallery; DVD-ROM features: Howard Zinn biography; Recommended reading list; Transcription of the Boston Common audio speech [PDF files require a DVD-ROM drive and Adobe Acrobat]; About First Run Features [text feature].
Keywords: Zinn, Howard, -- 1922-2010.; Historians -- United States -- Biography; Labor movement -- United States -- History -- 20th century; Civil disobedience -- United States -- History -- 20th century; Peace movements -- United States -- History -- 20th century; United States -- History -- 1945- -- Philosophy; Biographical films; Documentary films